2017
DOI: 10.3892/ijmm.2017.3006
|View full text |Cite
|
Sign up to set email alerts
|

A novel damage mechanism: Contribution of the interaction between necroptosis and ROS to high glucose-induced injury and inflammation in H9c2 cardiac cells

Abstract: Recently, a novel mechanism known as 'programmed necrosis' or necroptosis has been shown to be another important mechanism of cell death in the heart. In this study, we investigated the role of necroptosis in high glucose (HG)-induced injury and inflammation, as well as the underlying mechanisms. In particular, we focused on the interaction between necroptosis and reactive oxygen species (ROS) in H9c2 cardiac cells. Our results demonstrated that the exposure of H9c2 cardiac cells to 35 mM glucose (HG) markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 45 publications
(80 reference statements)
1
34
0
2
Order By: Relevance
“…The degenerative alterations in pancreatic acini in diabetic-induced rats may due to increased ROS production which are able to oxidation alteration and destruction of lipid in cellular membranes, particularly highly unsaturated fatty acids, by way of lipid peroxidation, result in suppression of the synthesis of protein and fragility of the zymogen granules (36). Particularly, production of ROS has been revealed to be influential in the etiology of diabetes by acting at the following various levels: 1) impairing uptake of glucose and pathways of insulin signaling (37, 2) modifying lipid metabolism and metabolic parameters (38,3) immune activation and raising inflammatory response (39) and (4) Both apoptosis and necroptosis that may culminate in tissue injuries in the kidneys, heart, retina, and nervous system (40).…”
Section: Discussionmentioning
confidence: 99%
“…The degenerative alterations in pancreatic acini in diabetic-induced rats may due to increased ROS production which are able to oxidation alteration and destruction of lipid in cellular membranes, particularly highly unsaturated fatty acids, by way of lipid peroxidation, result in suppression of the synthesis of protein and fragility of the zymogen granules (36). Particularly, production of ROS has been revealed to be influential in the etiology of diabetes by acting at the following various levels: 1) impairing uptake of glucose and pathways of insulin signaling (37, 2) modifying lipid metabolism and metabolic parameters (38,3) immune activation and raising inflammatory response (39) and (4) Both apoptosis and necroptosis that may culminate in tissue injuries in the kidneys, heart, retina, and nervous system (40).…”
Section: Discussionmentioning
confidence: 99%
“…These changes contributed to the elucidation of cholesterol‐induced necroptosis (Chtourou et al ., ). Furthermore, it was confirmed that the positive interaction between necroptosis and ROS is due to injury induced by high glucose levels and inflammation in H9C2 cardiac cells (Liang et al ., ).…”
Section: Programmed Cardiomyocyte Necrosis In Cardiovascular Diseasesmentioning
confidence: 97%
“…Acute or chronic high glucose in diabetes increases the production of ROS and activates apoptosis in the β-cells 15 . Both apoptosis and necroptosis have important roles in the progression of diabetic complications and they may culminate in tissue injuries in the heart, retina, kidneys, and nervous system 16 , 17 .…”
Section: Cellular Death and Diabetes Complicationsmentioning
confidence: 99%